2022
DOI: 10.1108/jfra-09-2021-0301
|View full text |Cite
|
Sign up to set email alerts
|

Does the CEO’s financial and accounting expertise affect the financial reporting quality? Evidence from an emerging economy

Abstract: Purpose This study aims to analyse the role of the financial and accounting expertise of the chief executive officer (CEO) on financial reporting quality (FRQ) in an emerging economy. Design/methodology/approach This study is based on data collected from a large sample of all non-financial companies listed on Vietnamese stock exchanges during the period 2016–2020 with 2,435 observations. FEM-ROBUST standard errors regression model is used to examine the relationship between the financial, accounting expertis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 102 publications
(265 reference statements)
0
2
0
4
Order By: Relevance
“…Akibat dari tindakan fraud yang buruk mendorong beberapa peneliti melakukan penelitian mengenai faktor faktor terjadinya fraud diantaranya (Davidson, 2022;Nhat et al, 2022;Wang et al, 2022). Penelitian sebelumnya berfokus pada faktor penyebab fraud dengan variabel seperti keragaman gender, whistle blowing, keahlian keuangan, kinerja keuangan, profitabilitas, namun beberapa temuan tidak konsisten.…”
Section: Pendahuluanunclassified
See 3 more Smart Citations
“…Akibat dari tindakan fraud yang buruk mendorong beberapa peneliti melakukan penelitian mengenai faktor faktor terjadinya fraud diantaranya (Davidson, 2022;Nhat et al, 2022;Wang et al, 2022). Penelitian sebelumnya berfokus pada faktor penyebab fraud dengan variabel seperti keragaman gender, whistle blowing, keahlian keuangan, kinerja keuangan, profitabilitas, namun beberapa temuan tidak konsisten.…”
Section: Pendahuluanunclassified
“…(Wang et al, 2022) menemukan bahwa wanita meningkatkan deteksi penipuan sehingga mengurangi perusahaan yang terlibat penipuan. Demikian juga keahlian keuangan memiliki dampak positif pada tindakan fraud (Nhat et al, 2022).…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…In the same context, Plumlee and Yohn (2010) advocated that CEOs with greater experience can effectively forecast future earnings and assets for the unit, as well as comprehend and apply legislation, regimes, and generally accepted accounting standards to create financial statements in the future. Ngo and Nguyen (2022) indicated that CEOs with financial accounting knowledge, on the other hand, gain greater confidence than novice CEOs, leading them to forecast higher profitability and apply positive accounting theories to achieve their goals. Their findings revealed that CEOs with financial and accounting backgrounds have more impact and intervention in earnings management, lowering FRQ.…”
Section: Ceo Accounting Backgroundmentioning
confidence: 99%